IMPLEMENTASI PROGRAM ALOKASI DANA DESA DALAM PENGEMBANGAN MODAL SOSIAL - Sabaruddin ' (Universitas Riau, 2015)
Implementation of the Village Fund Allocation Program in the Development of Social Capital. The research objective was to determine the allocation of the village fund program implementation in the development of social capital in the District of West Rangsang Meranti Islands District. The informants are leaders ADD program manager, community and public figures. Data collecting technique is interview, observation and documentation. Analysis of data using an interactive model. The results showed that the implementation of the policy of rural fund allocation program in the development of social capital has not reached maximum results.